Analysis of the Impact of Kijing International Port Development on the Welfare of Communities Affected by Land Acquisition - Ambarwati, Surya; Marini, Marini; Nurwijayanto, Nurwijayanto; Mukhlisah, Rafikah; Maniza, Eriska (LifeSciFi, 2023)
Kijing International Port is a National Strategic Project undergoing development in Mempawah Regency, Indonesia situated in close proximity to community settlements covering an area of 200 hectares. This development significantly impacts various economic and social sectors, including land acquisition and changes in livelihoods. The objective of this study is to assess the impact of the Kijing Port construction on residents affected by the land acquisition process. The research employs descriptive qualitative methods for data collection, including interviews, observations, and documentation. The informants for this study comprise five individuals with diverse livelihoods, selected through purposive sampling focusing on those affected by Kijing Port's land acquisition. The study's findings reveal that land acquisition has had a negative impact on the residents' lives. In the economic sector, the community's welfare has decreased as some have lost permanent employment. Regarding natural and social resources, the community faces challenges related to access to clean water and increased noise and air pollution. Infrastructure has also suffered, with some roads deteriorating quickly. Public perception indicates that, in general, the level of welfare and security was better before the construction of Kijing Port.